2013
DOI: 10.2217/bmm.13.106
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers Track the Progression of Nephropathy in Hypertensive and Obese Rats

Abstract: Aims To determine whether urinary biomarkers of acute kidney injury can be used to monitor the progression of chronic kidney injury in a rat model of hypertension and obesity. Materials & methods A suite of novel urinary biomarkers were used to track the progression of kidney damage in SHROB and SHR-lean rats. Results Urinary albumin, NAG, clusterin, osteopontin, RPA-1 and fibrinogen levels were significantly elevated over time and were closely associated with the severity of histopathologically determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…These biomarkers have also recently been used to detect adverse effects of chronic exposures to renal environmental toxicants such as metals and have allowed early detection of injury [Zhou et al, 2008;Prozialeck et al, 2009;Zhang et al, 2014]. Results present in Table V for the AKI biomarkers (IL-18; KIM-1 and NGAL) suggest that we may be seeing signs of early AKI in some members of this veteran cohort.…”
Section: Urinary Low Molecular Weight Proteins: Biomarkers Of Renal Pmentioning
confidence: 84%
“…These biomarkers have also recently been used to detect adverse effects of chronic exposures to renal environmental toxicants such as metals and have allowed early detection of injury [Zhou et al, 2008;Prozialeck et al, 2009;Zhang et al, 2014]. Results present in Table V for the AKI biomarkers (IL-18; KIM-1 and NGAL) suggest that we may be seeing signs of early AKI in some members of this veteran cohort.…”
Section: Urinary Low Molecular Weight Proteins: Biomarkers Of Renal Pmentioning
confidence: 84%
“…Changes in the urinary excretion of B2M, cystatin C, osteopontin, and uromodulin have been associated with varying forms of kidney injury, 27,33,[50][51][52][53][54][55]231 but were not different between preeclampsia cases and controls. Increased urine NGAL has been associated with acute kidney injury, 51,56,57 but we found levels to be decreased in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al tracked the progression of nephropathy in hypertensive and obese SHROB rats versus control hypertensive SHR-lean rats. Their results indicate that urinary NAG was elevated at week 33 and 36 in SHROB rats only, but not in SHR-lean rats at any time point [18], indicating that NAG may be an early reliable marker for obesity-related renal injury. Goknar et al demonstrated that urinary NAG was significantly elevated in obese children compared with lean controls [11].…”
Section: N-acetyl-beta-d-glucosaminidasementioning
confidence: 98%